2008
DOI: 10.1007/s12262-008-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Successfully treated stump appendicitis diagnosed by CT and ultrasonography

Abstract: Although rare, infl ammation of the appendiceal stump can occur and is still an important clinical entity. There has been a recent increase in interest in stump appendicitis. In this study a case of right lower quadrant pain in an 18-year-old man who underwent an appendicectomy 7 months previously is presented. Recurrent appendicitis was noted in an appendiceal stump during surgery which previously diagnosed by CT and ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been reported that almost 70% of patients with cecal diverticulitis underwent surgery based on preoperative diagnosis of acute appendicitis, and correct preoperative diagnosis was made in only 5.3% of 318 patients [ 8 ]. It is also reported that time interval from initial appendectomy to stump appendectomy may vary from 2 months to 50 years [ 1 , 9 ]. In the present case, stump appendicitis developed 6 months after first appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that almost 70% of patients with cecal diverticulitis underwent surgery based on preoperative diagnosis of acute appendicitis, and correct preoperative diagnosis was made in only 5.3% of 318 patients [ 8 ]. It is also reported that time interval from initial appendectomy to stump appendectomy may vary from 2 months to 50 years [ 1 , 9 ]. In the present case, stump appendicitis developed 6 months after first appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography has definite role in the diagnosis of residual appendicitis. [5,7] The diagnostic laparoscopy is quite useful while being also therapeutic. Despite all the diagnostic modalities, sometimes it is not possible to reach the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst ultrasound has been commonly used to diagnose acute appendicitis for over 30 years, 3 its utility in pre‐operative identification of stump appendicitis in patients post‐appendicectomy has only been documented more recently . Traditional sonographic criteria for diagnosing acute appendicitis have been applied to the appendiceal stump, with a transverse diameter greater than 6 mm, non‐compressibility and wall hyperaemia all being concerning for stump appendicitis. Secondary sonographic signs of acute appendicitis, such as echogenic peri‐appendiceal mesentery, can also indicate stump inflammation …”
Section: Introductionmentioning
confidence: 99%